2012
DOI: 10.19030/jabr.v28i5.7232
|View full text |Cite
|
Sign up to set email alerts
|

Mavenness And Salespeople Success: An Empirical Investigation

Abstract: <span style="font-family: Times New Roman; font-size: small;"> </span><p style="margin: 0in 0.5in 0pt; text-align: justify; mso-pagination: none;"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">The sales literature has examined many characteristics of highly successful salespeople but as yet has not evaluated the concept of mavenness in the context of sales.<span style="mso-spacerun: yes;"> </span>Mavens are persons who have a passionate des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sales leaders described the interaction between empathetic citizenship and analytical curiosity in terms of behaviors that embody mavenness (Eesley and Adidam, 2012). For example, analytical curiosity allows salespeople to gain more insight about the industry, their own products and the customers' issues, while salespeople high in empathetic citizenship readily share that knowledge with the client, further enhancing their credibility as experts in the field.…”
Section: Stabilizes Performance Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sales leaders described the interaction between empathetic citizenship and analytical curiosity in terms of behaviors that embody mavenness (Eesley and Adidam, 2012). For example, analytical curiosity allows salespeople to gain more insight about the industry, their own products and the customers' issues, while salespeople high in empathetic citizenship readily share that knowledge with the client, further enhancing their credibility as experts in the field.…”
Section: Stabilizes Performance Fluctuationsmentioning
confidence: 99%
“…Conversely, numerous direct relationships between specific traits and performance have been identified over the past decade. For example, Eesley and Adidam (2012) found that mavenness , the desire to share and a passion for one’s expertise in a particular area, was positively related to salesperson performance. Other context-specific personal traits found to positively influence salesperson performance include polychronicity , an innate preference for multitasking (Fournier et al , 2013), coachability (Shannahan et al , 2013) and proactivity (Sitser et al , 2013).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…For example, one study suggested that a salesperson's passion will carry over to their sales presentation and increase the authenticity and appeal of their message (Eesley and Adidam, 2012). Here, the salesperson develops various tactics that are seen by their customers to be persuasive.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%